Gestational Thrombocytopenic Patients in Our Center: Analysis of the Patients and Review of the Literature - Emel Ebru Özçimen (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Gestational thrombocytopenia is the most common cause of the thrombocytopenia in pregnancy. The aim of this study was to determine the prevalence of gestational thrombocytopenia (GT) among pregnant women in our center.